Is Paul also among the prophets? : an examination of the relationship between Paul and the Old Testament prophetic tradition in 2 Corinthians /: an examination of the relationship between Paul and the Old Testament prophetic tradition in 2 Corinthians. (©2012) - Unknown
No abstract available